Anticancer drugs and cardiotoxicity: the role of cardiomyocyte and non-cardiomyocyte cells - Koukorava, Chrysa; Ahmed, Katie; Almaghrabi, Shrouq; Pointon, Amy; Haddrick, Malcolm; Cross, Michael J. (Frontiers in Cardiovascular Medicine, 2024)
Cardiotoxicity can be defined as “chemically induced heart disease”, which can occur with many different drug classes treating a range of diseases. It is the primary cause of drug attrition during pre-clinical development and withdrawal from the market. Drug induced cardiovascular toxicity can result from both functional effects with alteration of the contractile and electrical regulation in the heart and structural changes with morphological changes to cardiomyocytes and other cardiac cells. These adverse effects result in conditions such as arrhythmia or a more serious reduction in left ventricular ejection fraction (LVEF), which can lead to heart failure and death. Anticancer drugs can adversely affect cardiomyocyte function as well as cardiac fibroblasts and cardiac endothelial cells, interfering in autocrine and paracrine signalling between these cell types and ultimately altering cardiac cellular homeostasis. This review aims to highlight potential toxicity mechanisms involving cardiomyocytes and non-cardiomyocyte cells by first introducing the physiological roles of these cells within the myocardium and secondly, identifying the physiological pathways perturbed by anticancer drugs in these cells.